Consensus-Driven Priorities for Firearm Injury Education Among Medical Professionals. (January 2022) - Hoops, Katherine; Fahimi, Jahan; Khoeur, Lina; Studenmund, Christine; Barber, Catherine; Barnhorst, Amy; Betz, Marian E.; Crifasi, Cassandra K.; Davis, John A.; Dewispelaere, William; Fisher, Lynn; Howard, Patricia K.; et al.
Abstract : Purpose: Firearm injury is a leading cause of morbidity and mortality in the United States. However, many medical professionals currently receive minimal or no education on firearm injury or its prevention. The authors sought to convene a diverse group of national experts in firearm injury epidemiology, injury prevention, and medical education to develop consensus on priorities to inform the creation of learning objectives and curricula for firearm injury education for medical professionals. Method: In 2019, the authors convened an advisory group that was geographically, demographically, and professionally diverse, composed of 33 clinicians, researchers, and educators from across the United States. They used the nominal group technique to achieve consensus on priorities for health professions education on firearm injury. The process involved an initial idea-generating phase, followed by a round-robin sharing of ideas and further idea generation, facilitated discussion and clarification, and the ranking of ideas to generate a prioritized list. Results: This report provides the first national consensus guidelines on firearm injury education for medical professionals. These priorities include a set of crosscutting, basic, and advanced learning objectives applicable to all contexts of firearm injury and all medical disciplines, specialties, and levels of training. They focus on 7 contextual categories that had previously been identified in the literature: 1 category of general priorities applicable to all contexts and 6 categories of specific contexts, including intimate partner violence, mass violence, officer-involved shootings, peer (nonpartner) violence, suicide, and unintentional injury. Conclusions: Robust, data- and consensus-driven priorities for health professions education on firearm injury create a pathway to clinician competence and self-efficacy. With an improved foundation for curriculum development and educational program-building, clinicians will be better informed to engage in a host of firearm injury prevention initiatives both at the bedside and in their communities. Abstract : Supplemental Digital Content is available in the text.